System Of Indicators For Economic Assessment Of Sustainable Regional Growth; The European Proceedings of Social & Behavioural Sciences (EpSBS); Vol. 35 : Research Paradigms Transformation in Social Sciences (RPTSS 2017) - Bannova K. A. Kristina Alekseevna; Balandina A. S.; Tyurina Yu. G.; Troyanskaya M. A. (2018, 2018)
Title screen